Using Daily Journals to Develop Writing Skills in Elementary School Students - Nur Istiqomah, Isna; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2024)
Writing activity is the activity of expressing ideas in written form as a means of communicating indirectly. Writing skills as one of the competencies in Indonesian language lessons is important for students, but do not receive enough attention. Through observation and interview activities, it was found that the writing skills of sixth (6th ) grade students at SD Negeri 02 Cikawung were still lacking. This research aims to form the habit of composing sentences in Indonesian through writing activities in the Daily Journal. This research used qualitative research methods. In this research, students carry out habitual activities in the form of writing in a daily journal such as reflecting on learning, writing down feelings, describing pictures, or writing based on a specified theme. After this activity, it was discovered that the habit of writing and writing ability had improved. This can be seen from the comparison of the initial survey and the final survey of activities, as well as the results of observations in students' daily journal notes. However, there are still some students who are not optimal in carrying out daily journal writing activities. Several inhibiting problems were reviewed to improve further activities.